2017
DOI: 10.7759/cureus.1195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Analgesia Drug Regimens for Pain Control During Extracorporeal Shock Wave Lithotripsy for Renal Stones: A Randomized Control Study

Abstract: IntroductionWith the increased use of extracorporeal shock wave lithotripsy (ESWL), the management of urolithiasis has become much convenient for the patients and the health care professionals alike. However, associated with the procedure is the common complaint of pain. No agreed upon pain management strategy has yet been developed for the procedure. We compared the effect of different analgesia drug regiments for pain control.MethodologyA randomised controlled trial was carried out in Shifa International Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Regardless of the effect of tamsulosin on analgesic use, many patients may require analgesics during the procedure. Waqas et al investigated the effect of different analgesic drug regimens on controlling the pain during the ESWL session (16). They found that the application of local 2% lignocaine gel did not affect the analgesic requirement during the ESWL procedure (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the effect of tamsulosin on analgesic use, many patients may require analgesics during the procedure. Waqas et al investigated the effect of different analgesic drug regimens on controlling the pain during the ESWL session (16). They found that the application of local 2% lignocaine gel did not affect the analgesic requirement during the ESWL procedure (16).…”
Section: Discussionmentioning
confidence: 99%
“…Waqas et al investigated the effect of different analgesic drug regimens on controlling the pain during the ESWL session (16). They found that the application of local 2% lignocaine gel did not affect the analgesic requirement during the ESWL procedure (16). According to their results, taking naproxen sodium with on-demand anesthesia could be a safe and feasible option for managing the procedural pain (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation